Effective Marketing Strategy Analysis to Increase Somethinc Product Sales Through Social Media - Aisyah Kayla (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
Digital marketing is crucial for company growth in the digital era, with social media becoming a key platform for brand building, awareness, and customer base expansion. This study analyzes the role of influencers in "Something's" digital marketing strategy on social media using a descriptive qualitative method. Data were collected through Google Forms and analyzed thematically. The results show that "Somethinc" successfully uses creative content, active follower interaction, and data analysis to optimize their marketing strategy. This research offers valuable insights for designing effective social media strategies to increase consumer engagement.